Mixed mode monolithic sorbent in pipette tip for extraction of ractopamine and clenbuterol prior to analysis by HPLC-UV and UHPLC-Q ExactiveTM Plus Orbitrap MS - Kesara Ar-sanork; Chanpen Karuwan; Nakin Surapanich; Prapin Wilairat; Duangjai Nacapricha; Patcharin Chaisuwan (Journal of Analytical Science and Technology, 2021)
Abstract This work developed a fast and simple method for the quantification of two important β-agonists, ractopamine (RAC) and clenbuterol (CLEN) in animal urines. The method was based on micro-extraction by a mixed mode monolithic material and analysis by HPLC-UV and UHPLC-Q ExactiveTM Plus Orbitrap mass spectrometer. A mixed functional monolith with nonpolar ester-based structure containing polar carboxylic groups was thermally synthesized in situ in the pipette tips. The material combines both hydrophobic and ionic interactions. Parameters including conditions and composition of reagents for the in-pipette tip monolith synthesis, as well as the extraction process, were investigated and optimized. The procedure for extraction is 800 μL washing solvent of 10:90 (v/v) ACN:water and 150 μL eluting solvent of 30:70 (v/v) ACN:200 mM acetate buffer pH 4.0. Extraction efficiencies of 92% and 100% for RAC and CLEN, respectively, were achieved within 5 min with total organic solvent consumption of 395 μL. The extracts of spiked cattle and swine urines were analyzed by HPLC-UV and UHPLC-Q ExactiveTM Plus Orbitrap mass spectrometer. Good recovery with acceptable precision was observed. The mass spectrometry data confirmed efficient matrix removal by the synthesized extraction sorbent allowing routine analysis by the HPLC-UV method.